(untitled) (Orthodontic Journal of Nepal, 2019)
Introduction: An accurate, reliable and stable method of accessing sagittal jaw relationship with cephalometric analysis is essential in orthodontic diagnosis and treatment planning. Many methods have been developed to assess antero-posterior jaw discrepancy but they all have some shortcomings including ANB angle. Thus the purpose of this study is 1) To provide mean values and standard deviations for ANB angle, Yen angle and W angle for a sample of skeletal Class I, II and III Chinese males and females malocclusion patients; 2) To verify the existence of sexual dimorphism; 3) To compare these three methods for assessing sagittal jaw relationship 4) To assess the correlation between these and 5) To find out which is the most reliable amongst them. Materials & Method: 120 pretreatment lateral cephalograms of Chinese patients, including both males and females between 18 to 25years old, were collected from the Department of Orthodontics; Wuhan Union Hospital which were divided into 3 groups as Class I, II and III skeletal pattern. Each pattern consists of 40 samples. The values of the males and females were compared with independent t-test while the inter-group comparisons were conducted with ANOVA and Tukey’s test. Pearson correlation test was performed to correlate between these angles. Result: There were no statistically significant differences between the mean values of these angles in male and female within the groups in all three classes. ANOVA analysis showed significant differences were found in ANB angle, Yen angle and W-angle in all the three Groups. Strong correlation existed between Yen angle and W angle. Conclusion: There is no existence of sexual dimorphism in our study. ANB angle is affected by growth of Nasion while Yen angle is affected by rotation of jaws. ANB angle is easy to assess while W angle is most stable and reliable.